THE EFFECT OF SHARIA FINANCIAL LITERACY, RELIGIOSITY, AND SERVICE QUALITY TOWARDS INTERESTING KSPPS PRODUCTS - Nafa Chalwa Salsabila; Ahmad Makhtum (I-Finance Journal, 2024)
The purpose of this research is to understand how Sharia Financial Literacy, Religiosity, and Service Quality can influence Members' interest in using KSPPS NU Dukun products. In this study, 231 respondents were involved using a quantitative methodology selected through the Proportional Random Sampling technique. An online questionnaire was used to collect data, and multiple linear regression was used to analyze it. The research results indicate that sharia financial literacy does not significantly affect member interest, while religiosity and service quality show significant influence. Simultaneously, the three variables influence member interest with a coefficient of determination of 56.5%. This study implies that increasing member interest in using KSPPS NU Dukun products is more effectively achieved through enhancing religiosity and service quality, while efforts to improve sharia financial literacy need to be accompanied by strategies to build trust and adjust products to the financial capabilities of prospective members.